2016
DOI: 10.1002/bem.22028
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic field at different stages of knee osteoarthritis in rats induced by low‐dose monosodium iodoacetate: Effect on subchondral trabecular bone microarchitecture and cartilage degradation

Abstract: The aim of the study was to investigate the efficacy of pre-emptive, early, and delayed pulsed electromagnetic field (PEMF) treatment on cartilage and subchondral trabecular bone in knee osteoarthritis (OA) rats induced by low-dose monosodium iodoacetate (MIA). Seventy-five 12-week-old male Sprague-Dawley rats were assigned to five groups: OA (n = 30), pre-emptive PEMF (n = 10), early PEMF (n = 10), delayed PEMF (n = 10), and control (n = 15). Osteoarthritis was induced by injecting 0.2 mg MIA in rat's right k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
1
23
0
2
Order By: Relevance
“…Similar results in rat models with osteoporosis have been observed; Jing et al [2014] showed that pre‐emptive PEMF can preserve subchondral trabecular bone and cortical bone microarchitecture, and inhibit bone loss. Yang et al [2017] demonstrated that pre‐emptive PEMF treatment has more a beneficial effect on subchondral trabecular bone microarchitecture compared with early and delayed PEMF treatment. Similar findings were also reported, that WBV treatment can maintain subchondral trabecular bone microarchitecture and avoid bone loss [Junbo et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results in rat models with osteoporosis have been observed; Jing et al [2014] showed that pre‐emptive PEMF can preserve subchondral trabecular bone and cortical bone microarchitecture, and inhibit bone loss. Yang et al [2017] demonstrated that pre‐emptive PEMF treatment has more a beneficial effect on subchondral trabecular bone microarchitecture compared with early and delayed PEMF treatment. Similar findings were also reported, that WBV treatment can maintain subchondral trabecular bone microarchitecture and avoid bone loss [Junbo et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PEMF can reduce the expression of the inflammatory cytokines interleukin‐1 (IL‐1β) and tumor necrosis factor‐α (TNF‐α), and downregulate matrix metalloproteinase (MMPs), which degrade ECM components and have a destructive effect on cartilage components [Wojdasiewicz et al, 2014; Zhou et al, 2017]. A previous study revealed the beneficial effect of pre‐emptive PEMF exposure on cartilage degeneration and subchondral bone loss for knee OA (KOA) in rats, and that the time point of treatment initiation is significant for treating OA [Yang et al, 2017]. Besides, clinical studies showed that PEMF can provide benefits for KOA patients in relieving pain and stiffness, and improving physical function and quality of life [Bagnato et al, 2016; Abdel‐Aziem et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…As well, the application of appropriately timed biophysical stimuli when engineering neocartilage [7] , and one less well studied related topic, examining upstream factors that can be harnessed to protect articular cartilage may help to avert progressive cartilage deterioration and degradation, and/or to produce functional cartilage. As well, the possible use of multiple, rather than single therapeutic strategies to attenuate the disease process [15] , including joint protection efforts in the face of attempts to stimulate neocartilage might prove especially helpful, as might careful mechanical or electrical stimulation of the affected osteoarthritic joint or both [102][103][104][105][106][107][108][109][110][111][112] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of EMFs to promote bone healing is supported by abundant preclinical literature that shows their action in rodent models of glucocorticoid‐ or ovariectomy‐induced osteoporosis [Zati et al, ; Bilotta et al, ; Chang and Chang, ; Jing et al, , ; Zhou et al, , , , b; Jiang et al, ; Lei et al, ], disuse osteoporosis [Shen and Zhao, ; Jing et al, ; Li et al, ], osteoporotic fractures [Androjna et al, ], osteoarthritis [Yang et al, ], diabetes‐associated bone architecture [Li et al, ], hyperthyroidism bone loss [Liu et al, ], and bone healing [Takano‐Yamamoto et al, ; Sarker et al, ; Landry et al, ; Fredericks et al, ; Midura et al, ; Taylor et al, ; Bilgin et al, ; Huegel et al, ].…”
Section: Therapeutic Effects Of Emfs On Bonementioning
confidence: 99%